PEMILIHAN LOKASI USAHA DAN PENGARUHNYA TERHADAP KEBERHASILAN USAHA JASA BERSKALA MIKRO DAN KECIL - Sandra Fitriyani; Trisna Murni; Sri Warsono (Management Insight: Jurnal Ilmiah Manajemen, 2018)
Abstract: The success of the business of entrepreneurs who are in the area behind Unib is very influenced by the factor of location or place of business. Place business which is getting closer to UNIB will be more and more consumers. A strategic place of business will have a profitable impact for businessmen, because the place of business is easily known and easily accessible by consumers, especially students. Research on the Selection of Business Locations and their Influence on Micro and Small Scale Business Success, aims to know the contribution in obtaining profit, and to analyze the influence of business environment factor and location cost on business success. The indicators used in the measurement of this study are competitor, consumer, rent, tax, profit rate and others. In this research use quantitative descriptive analysis method by using multiple regression statiistic tool. The result of the research shows that location selection based on business environment factor and location cost factor have influence to business success. The better the business environment conditions in that location will be easier to achieve success, and vice versa. The size of the costs incurred to obtain the business location, will determine the strategic place of business. A strategic place of business, will accelerate business success. This is supported by the perception of respondents that the success of the business is determined by: customer arrival rate / day, net profit growth, BEP time, rate of return, profit which all of the average value agree.Keyword: Business Environment, Location Cost, Business Success.